Cascading chemiresistive paper-based enzymatic biosensor for urea detection - Ronil J. Rath; Jacopo Giaretta; Thanh Phuong Hoang; Riccardo Zulli; Syamak Farajikhah; Sepehr Talebian; Sina Naficy; Fariba Dehghani (Sensors and Actuators Reports)
The conventional approach for diagnosing high risk metabolic disorders, such as chronic kidney disease (CKD), involves drawing a blood sample, which necessitates access to a centralized facility, making it undesirable for frequent urea monitoring. Alternative biological fluids, such as saliva, have demonstrated potential as non-invasive mediums for CKD monitoring due to the strong correlation between blood urea and salivary urea levels, indicating their suitability for point-of-care test kits. In this study, we present an innovative chemiresistive paper-based enzymatic sensor that utilizes a combination of urease and polystyrene sulfonate (PSS) to measure urea. This sensor detects urea over a broad concentration range (10–110 mg/dl), encompassing the salivary urea levels found in both healthy (20±10 mg/dl) and diseased (100±10 mg/dl) individuals. Furthermore, the sensor’s response to urea remains unaffected by the presence of interfering molecules in saliva such as metabolites, proteins, sugars and acids. The stability and response time of the sensor were also assessed under various temperatures, as encountered during storage. Overall, the sensor developed in this study offers a promising solution for creating a rapid, scalable, cost-effective, and user-friendly point-of-care monitoring test kit for urea screening in resource-limited setting with restricted access to healthcare facilities.